Experiments with force and motion - Uttley, Colin (New York : Gareth Stevens Pub., 2010)
Contains step-by-step instructions for science experiments that explain the principles of force and motion.
Jet boat -- On a roll! -- Human gyroscope -- Pendulum painter -- Twin pendulums -- Bend and bow -- Building a ramp -- Making a lever -- Pulling with a pulley -- Weighing water -- Blowing bubbles.
Includes bibliographical references (p. 31) and index.
5.4
3-6
3-6
Keywords: Force and energy -- Experiments -- Juvenile literature; Motion -- Experiments -- Juvenile literature; Force and energy -- Experiments; Motion -- Experiments; Science -- Experiments; Force and energy -- Experiments; Motion -- Experiments; Science -- Experiments